Fashion as an Expression of Cultural Identity in the Digital Age - Wardaya, Awwali Ibnu; Bestari, Afif Ghurub; Sulistiyanto, Sulistiyanto; Kindiasari, Aktansi (Utan Kayu Publishing, 2024)
Fashion has long been a powerful medium for expressing cultural identity, reflecting various communities' values, traditions, and social dynamics. This expression has evolved dramatically in the digital age, shaped by the pervasive influence of technology and social media. This study explores how fashion serves as a conduit for cultural identity in the contemporary digital landscape. It examines the interplay between traditional fashion practices and modern digital platforms. It highlights how individuals and communities use fashion to navigate and assert their cultural identities in an increasingly globalised world. The research investigates the role of digital platforms, such as Instagram, TikTok, and fashion blogs, in disseminating and transforming cultural fashion trends. These platforms provide a space for cultural exchange and the democratisation of fashion, allowing underrepresented voices to showcase their heritage and creativity. Additionally, the study delves into the impact of virtual fashion shows, digital influencers, and online retail on cultural identity expression. It considers how these elements contribute to preserving and evolving traditional fashion practices. Furthermore, the research addresses the complexities of cultural appropriation in the digital age, where fashion trends can be rapidly adopted and commercialised, often detached from their cultural significance. By analysing case studies and engaging with fashion designers, influencers, and consumers, the study offers insights into the ethical considerations and responsibilities involved in cultural fashion representation. The findings suggest that while digital platforms can facilitate celebrating and sharing cultural identities, they pose challenges related to authenticity, appropriation, and commercialisation. This duality underscores the need for a nuanced understanding of fashion as a cultural expression in the digital era. The study concludes with recommendations for fostering a more inclusive and respectful digital fashion ecosystem that honours and preserves cultural identities while embracing innovation and diversity. Through this exploration, the research aims to contribute to the broader discourse on cultural identity, fashion, and digital media, offering valuable perspectives for academics, industry professionals, and cultural advocates.